Do Environmental Performance, Feminism in Commissioner, Female Audit Committee, and Corporate Visibility Affect Corporate Environmental Disclosure? - Ardillah, Kenny (JASF: Journal of Accounting and Strategic Finance, 2022)
The company should not separate developing business activities from society's externalenvironment. Instead, the companies should protect the external environment, so manycompanies need to improve the sustainability of their companies to be better through corporate environmental disclosure. This study aims to examine and analyze the effect of environmental performance, feminism in commissioners, female audit committees, and corporate visibility towards corporate environmental disclosure, controlled by profitability and liquidity. One hundred samples were obtained from the mining companies listed on the Indonesia Stock Exchange from 2015 to 2019 and analyzed using the multiple linear regression method. This study proved that female audit committees could positively influence corporate environmental disclosure. On the other hand, this study found that environmental performance, feminism in commissioners, and corporate visibility couldn't affect corporate environmental disclosure. This result of the study can be used by the company's management to help companies provide more thorough supervision of decisions made by management related to social responsibility activities carried out by the female audit committee and monitor the quality of environmental disclosure more effectively. For investors, the results of this study are expected to provide information to investors about the importance of female audit committee members' existence in supporting the community's welfare.